Guerrilla Project Management. - Hanley, Kenneth T. (Berrett-Koehler Publishers, Incorporated, 2010)
A Fast, Flexible Approach to Managing Any Project ' Right Here, Right Now! To manage effectively in today's complex project environment, you need a framework of project management (PM) competencies, processes, and tools that can be put to use immediately and that flexes and scales to meet the needs of any project. InGuerrilla Project Management, Ken Hanley emphasizes key project management competencies, including managing stakeholders effectively, assessing risk accurately, and getting agreement on the objective measures of project success. Focusing on these and other competencies as well as effective PM processes and tools, Hanley presents an alternative approach to project management that is light, fast, and flexible ' and adapts readily to the many changes every project manager faces. Offering tips and techniques on topics ranging from communication and reporting practices to risk mitigation, this practical book is organized to allow readers to work through all aspects of a project or quickly find answers to specific problems. This isthego-to guide for today's nimble project manager!